2006
DOI: 10.1108/14757700610712471
|View full text |Cite
|
Sign up to set email alerts
|

Accounting research in the French language area – second half of the 20th century

Abstract: Purpose -This paper seeks to offer a survey of accounting publications and research in the French literature from 1950 to the end of the twentieth century. Design/methodology/approach -The methodology is that of literary research, review and critique. Findings -Finds that over the period mentioned different aspects of accounting research have been examined in the literature -academic, social, matrix, events, historical. The leading researchers in these fields are covered in detail. Originality/value -Succeeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It is noteworthy that none of the 91 studies identified as accounting addressed the environmental matter. Degos and Mattessich (2006) conducted a survey on the accounting publications in the French specialized literature between 1950 and 2000. The authors identified that different aspects of accounting research were examined in this period, such as the academic, social, matrix, events and history areas.…”
Section: Studies On Accounting and Costsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that none of the 91 studies identified as accounting addressed the environmental matter. Degos and Mattessich (2006) conducted a survey on the accounting publications in the French specialized literature between 1950 and 2000. The authors identified that different aspects of accounting research were examined in this period, such as the academic, social, matrix, events and history areas.…”
Section: Studies On Accounting and Costsmentioning
confidence: 99%
“…The authors identified that different aspects of accounting research were examined in this period, such as the academic, social, matrix, events and history areas. Degos and Mattessich (2006) believe that the most important accounting subarea in France in that period was the Chart of Accounts together with its revisers, particularly with European countries in their legislative processes of standardization and harmonization. In the perspective of the authors, in the second half of the 20 th century, the French influence on the accounting theory decreased partially because of the rise of the English accounting literature and the excessive focus on standardization; consequently, the academic research was neglected.…”
Section: Studies On Accounting and Costsmentioning
confidence: 99%
See 1 more Smart Citation